2008
DOI: 10.1002/syn.20529
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatments regulate matrix metalloproteinases‐2 and ‐9 (MMP‐2/MMP‐9) and tissue inhibitors of the metalloproteinases (TIMPS 1–4) in the adult rat hippocampus

Abstract: Antidepressants induce structural remodeling in the adult hippocampus, including changes in dendritic arbors, axonal sprouting, neurogenesis, and endothelial cell proliferation. Such forms of structural plasticity take place in the context of the extracellular matrix environment and are known to be regulated by matrix metalloproteinases (MMPs), in particular MMP-2/9, and their endogenous regulators, the tissue inhibitors of the metalloproteinases (TIMPs 1-4). Given the hippocampal structural remodeling associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…In addition, we demonstrate that fluoxetine affected the conversion of Pro-TGF-β1 into active TGF-β1, likely through the activation of MMP-2. The involvement of MMP-2 in fluoxetine activity is in line with the suggestion that extracellular matrix modifying enzymes contribute to antidepressant-mediated structural plasticity in the hippocampus (Benekareddy et al, 2008; Lee et al, 2014). The evidence that inhibiting astrocytes MMP-2 resulted into a lack of neuroprotection against Aβ toxicity supported the role of MMP-2 in fluoxetine-induced TGF-β1 release.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we demonstrate that fluoxetine affected the conversion of Pro-TGF-β1 into active TGF-β1, likely through the activation of MMP-2. The involvement of MMP-2 in fluoxetine activity is in line with the suggestion that extracellular matrix modifying enzymes contribute to antidepressant-mediated structural plasticity in the hippocampus (Benekareddy et al, 2008; Lee et al, 2014). The evidence that inhibiting astrocytes MMP-2 resulted into a lack of neuroprotection against Aβ toxicity supported the role of MMP-2 in fluoxetine-induced TGF-β1 release.…”
Section: Discussionsupporting
confidence: 84%
“…It is actually possible that this high dose of Fluoxetine may be activating alternative immunomodulatory or antiinflammatory pathways that are responsible for the authors’ observations and that are overcoming the effects on serotonin metabolism. Indeed Branco-de-Almeida et al showed that Fluoxetine inhibited IL-1β and COX-2 mRNA and metalloprotease (MMP) 9 activity in their model, and, consistently with these findings, it has been reported that 5 mg/kg i.p Fluoxetine can reduce the expression of MMP 2 and 9 in rat hippocampus [58] and 10 mg/kg i.p. Fluoxetine inhibits the expression of MMP 2, 9 and 12 after spinal cord injury in mouse [59].…”
Section: The Wnt Connectionmentioning
confidence: 79%
“…Our previous study showed that the serotonin-induced mitogenesis of PASMCs is mediated by SERT, in which the signal transduction for serotonin is dependent on the ERK1/2 pathway [14] . Benekareddy et al also reported that fluoxetine regulates MMP-2/ MMP-9 and TIMP1-4 in the adult rat hippocampus [31] . Taken this information and the present results together, we believe that fluoxetine-induced regulation of MMP-2, 9/TIMP-1, 2 is closely related to the inhibition of ECM remodeling, in which the serotonin intracellular signal pathway might be involved.…”
Section: Discussionmentioning
confidence: 99%